1963
DOI: 10.2134/agronj1963.00021962005500030008x
|View full text |Cite
|
Sign up to set email alerts
|

Method and Rate of Applying Zinc Sulfate for Corn on Zinc‐Deficient Soil in Western Nebraska1

Abstract: Synopsis Application of 5 pounds of Zn per acre broadcast and plowed under before planting increased early growth and grain yield. Other methods of application were less effective. Greater rates of application increased Zn concentration in young and nearly mature corn. Small amounts of N banded with ZnSO4 enhanced the effectiveness of ZnSO4. Yields of corn grain were related to Zn concentration of the index leaf.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

1971
1971
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 3 publications
(3 reference statements)
0
8
0
1
Order By: Relevance
“…This research indicated that more than 13.6 kg Znjha as broadcast ZnS0 4 was required to obtain maximum corn grain yield on the soil (Table 3). These data show that a higher level of broadcast ZnS0 4 than normally used (2,3,7,13,16,19) may be required to correct Zn deficiency of corn on some near-neutral soils containing high amounts of available P (Table 1).…”
Section: Yieldsmentioning
confidence: 83%
“…This research indicated that more than 13.6 kg Znjha as broadcast ZnS0 4 was required to obtain maximum corn grain yield on the soil (Table 3). These data show that a higher level of broadcast ZnS0 4 than normally used (2,3,7,13,16,19) may be required to correct Zn deficiency of corn on some near-neutral soils containing high amounts of available P (Table 1).…”
Section: Yieldsmentioning
confidence: 83%
“…In addition, the early to mid‐vegetative phase applications could greatly impact the PNURs for Mg, Zn, and Mn before silking time and then consequently modify the ENARs. For Zn, Pumphrey et al (1963) demonstrated that preplant Zn application was effective in promoting early growth, and those benefits were translated into yield at the end of the season. More research should be performed to define optimum timing, rates, placement, and sources for applying micronutrients, considering each nutrient as an individual case.…”
Section: Resultsmentioning
confidence: 99%
“…Cool, wet environmental conditions that occur before the permanent flood is established may also exacerbate Zn deficiency of seedling rice, especially when rice is seeded very early (Norman et al, 2003). Although the flooded soil conditions used to grow rice play an important role in the occurrence and diagnosis of Zn deficiency, delaying Zn application until after crop emergence has also been shown to reduce yield potential of corn (Pumphrey et al, 1963). Once seedlings become Zn deficient, some minimum amount of time is likely needed for the uptake and translocation of foliar‐applied Zn and subsequent restoration of normal plant growth and metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Pumphrey et al (1963) showed that foliar application of ZnSO 4 to corn ( Zea mays L.) seedlings was generally less effective than preplant soil‐applied Zn. Wells et al (1973) reported the results of more than 20 Zn fertilization trials conducted in Arkansas, which included granular and liquid formulations of Zn applied across a wide range of Zn application rates and times.…”
mentioning
confidence: 99%